Improving child nutrition in disasters by developing a modeled disaster preparedness nutrition education curriculum - Adeoya, Akindele Abimibayo; Egawa, Shinichi; Adeoya, Adebayo Sunday; Nagatomi, Ryoichi (Frontiers in Public Health, 2023)
In contemporary global society, largely because of climate change and other natural and humaninduced hazards, disasters are an almost daily occurrence. The nutritional impact of disasters on children results in long-term physical and mental health problems. As children are one of the most vulnerable demographic groups, they must be empowered with disaster preparedness nutrition knowledge, and the skills and motivation to survive, prevent/reduce malnutrition, and maintain good health during disasters. A disaster preparedness nutrition education program (DPNEP) was developed in this study to improve children's nutrition in daily life and during disasters through student-centered education. A consultative approach was used to synthesize the knowledge of a diverse group of four experts in disaster medicine and management, public health, education, and food and nutrition sciences to reach a consensus through discussion. A model DPNEP was developed by targeting grade 4 and 5 students and using interactive teaching methods. This can lead to the implementation of continuous nutrition education to empower children to make healthy food choices in daily life and reduce the risk of disaster-nutrition-related morbidity and mortality. Furthermore, once children acquire the necessary information, they are likely to share this knowledge with their families and communities, thereby enhancing society's resilience.